2001
DOI: 10.1038/35075076
|View full text |Cite
|
Sign up to set email alerts
|

BDNF controls dopamine D3 receptor expression and triggers behavioural sensitization

Abstract: Brain-derived neurotrophic factor (BDNF), like other neurotrophins, is a polypeptidic factor initially regarded to be responsible for neuron proliferation, differentiation and survival, through its uptake at nerve terminals and retrograde transport to the cell body. A more diverse role for BDNF has emerged progressively from observations showing that it is also transported anterogradely, is released on neuron depolarization, and triggers rapid intracellular signals and action potentials in central neurons. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
339
4
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(369 citation statements)
references
References 29 publications
14
339
4
3
Order By: Relevance
“…76,77 We found that administration of antipsychotic drugs, such as haloperidol and risperidone, decreased levels of BDNF in the frontal and occipital cortex and hippocampus, whereas only haloperidol, which mainly acts on the dopamine(DA)-D 2 and D 3 receptors, significantly reduced the number of TrkBimmunoreactive neurons in the hippocampus, substantia nigra and ventral tegmental area. 78 These studies support the hypothesis that antipsychotic drugs exert their effect, at least in part, by modifying the synthesis and distribution of BDNF in selected brain regions.…”
Section: Bdnf and Animal Models Of Schizophreniasupporting
confidence: 60%
“…76,77 We found that administration of antipsychotic drugs, such as haloperidol and risperidone, decreased levels of BDNF in the frontal and occipital cortex and hippocampus, whereas only haloperidol, which mainly acts on the dopamine(DA)-D 2 and D 3 receptors, significantly reduced the number of TrkBimmunoreactive neurons in the hippocampus, substantia nigra and ventral tegmental area. 78 These studies support the hypothesis that antipsychotic drugs exert their effect, at least in part, by modifying the synthesis and distribution of BDNF in selected brain regions.…”
Section: Bdnf and Animal Models Of Schizophreniasupporting
confidence: 60%
“…(2016) have shown how the parents’ serotonin transporter genotype moderates the association between child noncompliance and parental negativity. We chose to focus on the brain‐derived neurotrophic factor (BDNF), which has been associated with both the serotonergic (Eaton, Staley, Globus, & Whittemore, 1995; Mamounas, Blue, Siuciak, & Altar, 1995) and dopaminergic systems (Guillin et al., 2001; Küppers & Beyer, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…8,9 BDNF has regulatory effects on multiple neurotransmitter systems, including serotonin 10 and dopamine, 11 and maybe involved in the etiology of stress-related disorders, such as depression and PTSD. Chronic administration of antidepressants, including selective serotonin reuptake inhibitors, increases BDNF expression in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%